Structural and Optical Properties of CdSe/CdTe Core-Shell Quantum Dots. (22nd January 2022) - Ramalingam, G.; Ragupathi, C.; Rangasamy, Baskaran; Colak, I.; Vetrivelan, V.; Poudineh, Neda; Ravindran, Balasubramani; Chang, Soon Woong; Gengan, Robert M.
Abstract : A simple hydrothermal method is developed for the synthesis of high-quality type II core-shell CdSe/CdTe quantum dots (QDs). The XRD results reveal the formation of mixed phases of CdSe and CdTe with a grain size of 12.6 nm. SEM morphology confirms the uniformly distributed nanoscale CdSe/CdTe with no agglomeration. EDX confirms the elemental presence of Cd, Se, and Te in the compound. TEM results suggest that the size of spherical CdSe/CdTe core-shell QDs is in the range of 8 10 nm. Significant results of the SAED pattern confirm the core and shell components as CdSe and CdTe, respectively. The correlation between the synthesis procedures and the corresponding structures of the core-shell CdSe/CdTe QDs is discussed. The demonstrated monodispersed lattice structure of core-shell CdSe/CdTe QDs has excellent PL emission properties at λ emi 585 nm which is suitable for photovoltaic applications. The UV-Vis absorption bands at 455 nm and 560 nm confirm exciton emission due to the type II matrix of CdSe/CdTe QDs.